Identification, molecular characterization and expression analysis ofRPL24genes in three Cucurbitaceae family members: cucumber, melon and watermelon - Baloglu, Mehmet Cengiz; Ulu, Ferhat; Altunoglu, Yasemin Celik; Pekol, Sefa; Alagoz, Gamze; Ese, Okan (Informa UK Limited, 2015)
Ribosomal proteins are crucial for the proper growth and development of any organism, including plants. The ribosomal protein L24 (RPL24) is found in the large subunit of the ribosome and is responsible for the stabilization of the peptidyl transferase activity. Although RPL24 gene has been individually identified in different organisms, little is known about the genome-wide survey and expression patterns of R24 genes in Cucurbitaceae family members. We identified seven Cucurbitaceae RPL24 genes from cucumber, melon and watermelon. They were phylogenetically clustered into seven major groups. Gene structure and motif composition are relatively conserved in each group. Three-dimensional homology modelling of RPL24 proteins was performed with higher confidence level. CmRPL24-01 was isolated from melon and characterized at a molecular level. The regulation of ribosomal proteins in melon under drought stress conditions was also studied. The expression of CmRPL24-01 gene increased in melon leaf tissue at 3 h u...
Keywords: 2. Zero hunger; 15. Life on land; 7. Clean energy; 6. Clean water; 3. Good health